Effects of the playing surface on plantar pressures during the first serve in tennis - Girard, O.; Micallef, J. P.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2010)
Purpose: This study aimed at examining the influence of different playing surfaces on in-shoe loading patterns in each foot (back and front) separately during the first serve in tennis. Methods: Ten competitive tennis players completed randomly five first (ie, flat) serves on two different playing surfaces: clay vs GreenSet. Maximum and mean force, peak and mean pressure, mean area, contact area and relative load were recorded by Pedar insoles divided into 9 areas for analysis. Results: Mean pressure was significantly lower (123 ± 30 vs 98 ± 26 kPa; -18.5%; P < .05) on clay than on GreenSet when examining the entire back foot. GreenSet induced higher mean pressures under the medial forefoot, lateral forefoot and hallux of the back foot (+9.9%, +3.5% and +15.9%, respectively; both P < .01) in conjunction with a trend toward higher maximal forces in the back hallux (+15.1%, P = .08). Peak pressures recorded under the central and lateral forefoot (+21.8% and +25.1%; P < .05) of the front foot but also the mean area values measured on the back medial and lateral midfoot were higher (P < .05) on clay. No significant interaction between foot region and playing surface on relative load was found. Conclusions: It is suggested that in-shoe loading parameters characterizing the first serve in tennis are adjusted according to the ground type surface. A lesser asymmetry in peak (P < .01) and mean (P < .001) pressures between the two feet was found on clay, suggesting a greater need for stability on this surface.